2021
DOI: 10.1042/cs20201574
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in angiotensin II-induced hypertension and kidney injury: role of AT1a receptors in the proximal tubule of the kidney

Abstract: In the present study, we tested the hypothesis that there are significant sex differences in angiotensin II (Ang II)-induced hypertension and kidney injury using male and female wild-type and proximal tubule-specific AT1a receptor knockout mice (PT-Agtr1a-/-). Twelve groups (n=8-12 per group) of adult male and female wild-type and PT-Agtr1a-/- mice were infused with a pressor dose of Ang II via osmotic pump for 2 weeks (1.5 mg/kg/day, i.p.) and simultaneously treated with or without losartan (20 mg/kg/day, p.o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(43 citation statements)
references
References 48 publications
1
42
0
Order By: Relevance
“…In a similar nitric oxide inhibition-induced hypertension model in rats, blood pressures between male and female groups were not significantly different until after Day 15 [23]. In a murine A2HTN model where angiotensin II was administered at a rate of 1.5 mg/kg/day, blood pressures were not significantly different throughout the 14-day study [24]. In past studies, we have observed compensatory renal lymphangiogenesis in both male and female LHTN and A2HTN mice, and renal lymphatic vessel density was not significantly altered between sexes [9,11].…”
Section: Discussionmentioning
confidence: 84%
“…In a similar nitric oxide inhibition-induced hypertension model in rats, blood pressures between male and female groups were not significantly different until after Day 15 [23]. In a murine A2HTN model where angiotensin II was administered at a rate of 1.5 mg/kg/day, blood pressures were not significantly different throughout the 14-day study [24]. In past studies, we have observed compensatory renal lymphangiogenesis in both male and female LHTN and A2HTN mice, and renal lymphatic vessel density was not significantly altered between sexes [9,11].…”
Section: Discussionmentioning
confidence: 84%
“…By contrast, deletion of AT 1a receptors in all tissues of the body led to an approximately 30 ± 5 mmHg lower systolic, diastolic, and mean arterial blood pressure in global Agtr1a -/- mice [ 11 , 16 , 28 , 55 ]. No significant sex differences in this basal blood pressure phenotype were observed in either global Agtr1a -/- or proximal tubule-specific PT- Agtr1a -/- mice [ 12 , 28 ]. The blood pressure-lowering effect in PT- Agtr1a -/- mice was associated with significant diuretic and natriuretic responses and increases in the basal glomerular filtration rate as well as the pressure-natriuresis response due to the inhibition of Na + and fluid reabsorption in the proximal tubules ( Figure 2 ) [ 28 , 104 , 105 ].…”
Section: At 1 (At 1a ) Receptor...mentioning
confidence: 99%
“…The development of Ang II-induced hypertension has been extensively studied in different animal models with AT 1 (AT 1a ) receptors playing the fundamental role [ 12 , 27 , 71 , 97 , 104 ]. AT 1 (AT 1a ) receptors are expressed widely, although to different levels, in the brain, adrenal glands, and cardiovascular and kidney tissues; thus, the mechanisms underlying Ang II-induced hypertension are expected to involve different tissues or pathways [ 16 , 39 ].…”
Section: At 1 (At 1a ) Receptor...mentioning
confidence: 99%
See 2 more Smart Citations